Theoretical foundations of the formation of the professional and moral culture of the future teacher - Sherzod Sultonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is intended to highlight the essence, components, factors, and pedagogical prerequisites for the formation of the professional and moral culture of the future teacher.